Papua New Guinea Economic Update, February 2022 : Navigating a Fragile Recovery - World Bank (Washington, DC, 2022)
Reflecting a strong global economic rebound, Papua New Guinea (PNG) reversed its downward economic growth trajectory in 2021. The World Bank estimates that the PNG economy contracted by 3.5 percent in 2020 before returning to positive economic growth of 1 percent in 2021. Domestic agricultural production continued unabated through the pandemic, and the Coronavirus disease 2019 (COVID-19) related mobility restrictions were not as severe as in some other economies. However, gross domestic product (GDP) growth has lagged global and regional averages. PNG’s economic performance in 2021 was constrained by falling gold and liquefied natural gas (LNG) production that resulted in a decline in extractive sector output for a second consecutive year. Despite reversing the trajectory of the widening fiscal deficit, it remained large at over 7 percent GDP. Public debt exceeded 50 percent of GDP, and the country is at high risk of debt distress, according to the latest World Bank - International Monetary Fund (IMF) debt sustainability analysis. Despite an accommodative monetary policy, private sector lending remained flat due to subdued economic conditions. The current account surplus remained substantial owing to depressed imports and high commodity prices. However, due to the large debt repayments of the extractive sector, shortages of foreign currency remain a key problem for PNG’s economy.